Propiedades nutricionales de la carne de pavo americano big-6 con una dieta balanceada más la adición de col fresca (brassica oleracea var. Capitata) en la fase de engorde - Muñoz Montoya, Jairo Antonio (2016)
This research project was carried out at the Experimental Farm "La Maria", owned by the State Technical University of Quevedo (UTEQ) in the Poultry Program, located at km 7 ½ Quevedo route - El Empalme, lasting 43 days (November 9 to December 21, 2015), pursuing the following objectives: a) to determine the productive performance of American turkeys Big-6 (weight gain, live weight, feed intake, feed conversion and carcass yield), b) determine the nutritional characteristics of turkey meat supplemented with cabbage, c) know the organoleptic characteristics of turkey meat supplemented with cabbage d) to determine the profitability of treatments. The diets used were (T1): Balanced UTEQ; (T2): addition of 5% of cabbage; (T3) addition of 10% of al. a completely randomized design (CRD) with four replications was applied. 60 turkeys were used without sexing in the fattening stage where the T3 treatment had the best (P <0.05) weight gain (155.32 g animal-1 day-1), feed intake (541.80 g animal-1 day-1 ), feed conversion (3.46), carcass yield (88.72%) and a return of 95.00 %. The highest percentage of protein you record the treatment T2 (24.8%), while the lowest percentage of fat T3 (0.60%) treatment, however, the analysis Ash lower values were presented in the T2 (1.04% ) and the lowest humidity the present T1 (73.94%) as the organoleptic characteristics of meat proceeded to perform a non-parametric analysis of affectivity with hedonic intensity scales attributes where it was determined that the T3 presented the best features for what the methodology applied in this research yielded a better quality meat